A The Invasion of Patriarchal Ghost into Different Woman Representations: An Analysis of the Film, Motherland - Sever, Hasan; Açıkalın, Neriman (Journal of Applied And Theoretical Social Sciences, 2025)
Introduction: This study attempts to read the phenomenon of gender through the film Motherland and examines three important figures of the patriarchal social order. The first of these is Halise as the carriers and implementers of the dominant ideology; the second is Emine, who is convinced of the illusion of male domination and cannot realize her feminine power; and the third is Nesrin, who tries to oppose all dominant patriarchal values. The aim of the study is to discuss the identities of women, which overlap in some places and completely separate in others, in a sociological context through three main characters. Method: The film was analyzed in the context of women's intersectionality by reading the concepts of patriarchal bargaining, family institution and male domination through its three main characters. The scenes, symbols and dialogues in the film were addressed with a feminist analysis approach. Results or Findings: The character of Anne Halise negotiates with the patriarchal ideology and shapes her relationship with her daughter Nesrin. Nesrin is in constant conflict with her mother as a character who opposes the values ​​of the patriarchal ideology. Emine is represented as a figure who is made to feel absolute helplessness by the male power. Discussion or Conclusion: The film Motherland gains importance in terms of understanding how the patriarchal ideology, which hovers around women like a ghost and organizes and disciplines everything according to its own norms, is reproduced through women.